Simulating the Effect of Gas Channel Geometry on PEM Fuel Cell Performance by Finite Element Method. (2016) - Ionescu, Viorel
Abstract: Proton exchange membrane fuel cells (PEMFC) become in the last years an attractive alternative clean energy source and the main researches are oriented in order to understand how different cell parameters affects the performance of the fuel cell in real operating conditions and subsequently reduce the cost involved in prototype development. Comsol Multiphysics, a commercial solver based on the Finite Element Method (FEM) was used for developing a three dimensional model of PEMFC working at a high temperature of 150 ̊C. Cathode gas flow velocity influence on the cell performance was investigated at first. The effect of channel width and channel height on the current density at a cell voltage of 0.5 V was established, at various cathode gas flow velocities between 0.04 and 0.42 m/s. Local current density variation for cell geometries with three different channel widths (0.8, 1.2 and 1.6 mm) at three different channel heights (1, 2 and 3 mm) were computed at a cathode inlet flow velocity of 0.1 m/s and cell voltage of 0.3 V. Oxygen and water molar concentrations at cathode catalyst layer-GDL channel interface were also studied for specific gas channel geometries.